Facts and Challenges from the Great Recession for Forecasting and Macroeconomic Modeling - Ng, Serena; Wright, Jonathan H. (Journal of Economic Literature, 2013)
This paper provides a survey of business cycle facts, updated to take account of recent data. Emphasis is given to the Great Recession, which was unlike most other postwar recessions in the United States in being driven by deleveraging and financial market factors. We document how recessions with financial market origins are different from those driven by supply or monetary policy shocks. This helps explain why economic models and predictors that work well at some times do poorly at other times. We discuss challenges for forecasters and empirical researchers in light of the updated business cycle facts.